Training Strategies, Theories and Types - Wajdi Milhem; Khalil Abushamsieh; María Nieves Pérez-Aróstegui (Journal of Accounting, Business and Management (JABM), 2014)
This article aims to identify the concept of human resource training and to emphasize strategies, theories and kinds of training. The organizational strategy and training are very essential to show the benefits of using strategic view and perception of training, since by linking this strategy with human resource actively, particularly on training and development, it will contribute to the success and enrichment of the organizations. Training and development are also considered as continuous improving process that should be up to date to face the dynamic changes in workplace and to adopt training as a competitive advantage of the organization. Theories are important in choosing and implementation of training process approach on professional way. In the same time in this article we will focus on training kinds and development of these kinds which including E-learning and learning management system (LMS) as a methods of training delivery.